2019
DOI: 10.1152/jn.00319.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying chemoreflex stress on sympathetic neural recruitment strategies during apnea

Abstract: PURPOSE Sympathetic nervous system responses to voluntary apnea are increased by hypoxia and attenuated by hyperoxia. However, whether neural firing and recruitment strategies in response to apnea can be modified by hypoxia and/or hyperoxia were previously unknown. We examined the influence of chemoreceptor stimuli on sympathetic neural firing and recruitment strategies during voluntary end‐expiratory apnea. We hypothesized increases in the firing frequency and probability of low‐threshold axons during apnea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Compared to sympathetic stress elicited during orthostatic challenges (Badrov et al., 2015; Klassen et al., 2019, 2020) and chemical stimuli via end expiratory apnoea or intermittent hypercapnic hypoxia (Badrov et al., 2015; Klassen et al., 2019; Ott et al., 2020), acute isocapnic hypoxia produced a less robust sympathetic response. Indeed, acute (≥5 min) poikilocapnic hypoxia has been shown to have little effect on total AP cluster activity (Ott et al., 2019), supporting the notion that the type of neural reflex manoeuvre and intensity of sympathoexcitation influences the degree of sympathetic postganglionic neuronal recruitment (Charkoudian & Wallin, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Compared to sympathetic stress elicited during orthostatic challenges (Badrov et al., 2015; Klassen et al., 2019, 2020) and chemical stimuli via end expiratory apnoea or intermittent hypercapnic hypoxia (Badrov et al., 2015; Klassen et al., 2019; Ott et al., 2020), acute isocapnic hypoxia produced a less robust sympathetic response. Indeed, acute (≥5 min) poikilocapnic hypoxia has been shown to have little effect on total AP cluster activity (Ott et al., 2019), supporting the notion that the type of neural reflex manoeuvre and intensity of sympathoexcitation influences the degree of sympathetic postganglionic neuronal recruitment (Charkoudian & Wallin, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Smaller-sized APs are not only under weak baroreflex control (Klassen et al, 2020), but also express greater asynchronous firing patterns between bursts during periods previously considered 'neurally silent' (Klassen et al, 2019). Sympathetic activation during severe orthostatic (Badrov et al, 2015;Klassen et al, 2019Klassen et al, , 2020Salmanpour et al, 2011) and chemical (Badrov et al, 2015;Ott et al, 2019Ott et al, , 2020Steinback et al, 2010) stressors appears to be facilitated by both enhanced neural recruitment of previously latent, larger-diameter sympathetic axons and resetting of the arterial baroreflex to permit increased firing frequency of medium sized AP subpopulations (Klassen et al, 2020), in addition to reduced incidence of asynchronous AP activity (Klassen et al, 2019). However, the baroreflex governing strategies over varying-sized sympathetic axons that permit sLTF following hypoxia-induced chemoreflex activation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if transient hyperoxia had a direct effect on central mechanisms, then reductions in baseline muscle sympathetic nerve activity might be expected. Several investigations have shown that this is not the case ( Morgan et al, 1995 ; Ott et al, 2019 ; Querido et al, 2010 ).…”
Section: Factors That Impact the Magnitude Of Autonomic And Cardiovascular Plasticitymentioning
confidence: 97%
“…AP patterns were detected and extracted using wavelet-based methodology on the raw, band-pass-filtered neurogram using techniques developed in the laboratory of Dr. J. Kevin Shoemaker (60). As described previously (30,46), a continuous wavelet transform using a "mother wavelet" with the same morphology as a physiological postganglionic sympathetic AP was used for AP detection. APs were only extracted if they occurred within an integrated burst (i.e., 0.8 s around the peak of the burst).…”
Section: Participantsmentioning
confidence: 99%
“…The probability of 100% indicates clusters within the bin fired more than once in every integrated burst, whereas a probability less than 100% indicates the cluster did not fire multiple times in every burst. Because the number of total clusters varies by individual, normalization procedures were completed using methods published previously (5,30,46). Briefly, APs were normalized to the largest detected cluster (given a value of 100%).…”
Section: Participantsmentioning
confidence: 99%